2020
DOI: 10.3389/fmicb.2019.03033
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway and Viral Infections

Abstract: The Hippo signaling pathway is a novel tumor suppressor pathway, initially found in Drosophila. Recent studies have discovered that the Hippo signaling pathway plays a critical role in a wide range of biological processes, including organ size control, cell proliferation, cancer development, and virus-induced diseases. In this review, we summarize the current understanding of the biological feature and pathological role of the Hippo pathway, focusing particularly on current findings in the function of the Hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 87 publications
(134 reference statements)
0
50
0
Order By: Relevance
“…Accumulating evidence shows that the Hippo/YAP signaling pathway plays critical roles in a wide range of biological processes, including cell proliferation, apoptosis, and tumorigenesis ( 13 , 14 , 20 ). Dysregulation of YAP protein, the key factor in the Hippo pathway, has been implicated in viral transformation ( 21 ). Examples include hepatitis B virus (HBV), hepatitis C virus (HCV), human papillomavirus (HPV), Epstein–Barr virus, and Kaposi sarcoma-associated herpesvirus ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence shows that the Hippo/YAP signaling pathway plays critical roles in a wide range of biological processes, including cell proliferation, apoptosis, and tumorigenesis ( 13 , 14 , 20 ). Dysregulation of YAP protein, the key factor in the Hippo pathway, has been implicated in viral transformation ( 21 ). Examples include hepatitis B virus (HBV), hepatitis C virus (HCV), human papillomavirus (HPV), Epstein–Barr virus, and Kaposi sarcoma-associated herpesvirus ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that a variety of human viruses exert their carcinogenic function via the Hippo pathway ( 21 ). Known mechanisms of Hippo dysregulation in virus-infected cells include 1) up-regulation of YAP expression through activating its promoter ( 22 24 ), 2) inhibition of proteasome-dependent degradation of YAP protein ( 25 , 26 ), 3) inhibition of YAP phosphorylation to increase nuclear localization ( 26 , 27 ), and 4) suppression of the Hippo pathway through regulating the kinase activity of MST1/2 or LATS1/2 ( 28 ).…”
mentioning
confidence: 99%
“…Since the MAPK pathway plays a vital role in releasing pro-inflammatory cytokines (e.g., IL6 ) associated with myocardial dysfunction and acute lung injury, targeted inhibition of this pathway could attenuate SARS-CoV-2 infection [ 24 ]. In addition, therapeutic inhibition of the Hippo pathway component may provide a potential value for antiviral treatment [ 25 ]. Furthermore, it found that in COVID-19 patients, TGFβ stimulates the WNT/β-catenin pathway, leading to an increased risk of pulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in breast cancer, EBV infection also causes inactivation of the Hippo signaling pathway 62 . It also has been reported that when hepatitis C virus (HCV), infectious mollusc virus (MCV), mouse polyomavirus (MupyV), Kaposi Sarcoma-associated herpesvirus (KSHV), Zika virus (ZIKA) affecting host cells, the increase of YAP/TAZ expression activity could be found 63 .…”
Section: The Upstream Regulatory Network Of the Hippo Signaling Pathwaymentioning
confidence: 99%